Pengaruh Penambahan Zeolit Dan Kapur Pada Tanah Lempung Terhadap Direct Shear Test - Harnasus Kristanto Kadang Bua; Meti; Tangdialla, Lintje Tammu (Paulus Civil Engineering Journal, 2025)
In the process of building a construction, various difficulties can be encountered, including soil conditions that do not support being used as a basis for construction work. From this, researchers tried attempted to use direct shear testing to add lime and zeolite to clay soil in an effort to boost the soil's carrying capacity.  The purpose of this study is to use direct shear testing to ascertain the properties of the soil in Latuppa Village, Mungkajang District, Palopo City, as well as the impact of adding lime and zeolite to clay soil.  A mixture of 5% lime and varying amounts of 0%, 5%, 10%, and 15% zeolite were used in this test.  The two phases of this study were the 1) direct shear test and the 2) soil characteristics test.The soil is inorganic clay, according to the findings of tests conducted on its properties. The direct shear test results at point 1 of cohesion for the 5%+0% variation were 0.091 kg/cm2 and increased to the 5%+15% variation of 0.159 kg/cm2, the shear angle for the 5%+0% variation was 19.307° and increased to the 5%+15% variation of 26.691°. At point 2 the cohesion for the 5%+0% variation is 0.104 kg/cm2 and increases to the 5%+15% variation of 0.139 kg/cm2, the friction angle for the 5%+0% variation is 20.488° and increases to the 5%+15% variation of 26.860°. Likewise, at point 3, the cohesion obtained for the 5%+0% variation was 0.119 kg/cm2 and increased to the 5%+15% variation At 0.182 kg/cm2, the friction angle value rose to 25.521° for the 5%+15% variation from 19.785° for the 5%+0% variation.  Therefore, adding zeolite and lime can raise the cohesion value (c) and friction angle (ø) in the direct shear test.